1995
DOI: 10.1590/s0102-76381995000100002
|View full text |Cite
|
Sign up to set email alerts
|

Evolução clínica e comportamento da função ventricular no pós-operatório tardio da cardiomioplastia

Abstract: RESUMO : A cardiomioplastia tem sido proposta, como uma alternativa ao transplante cardíaco, no tratamento de pacientes com insuficiência miocárdica em fase avançada. O objetivo deste trabalho é estudar a evolução clínica e o comportamento da função ventricular no pós-operatório tardio desse procedimento em 34 pacientes portadores de cardiomiopatia dilatada, que foram operados no período de maio de 1988 a setembro de 1994. Vinte e sete pacientes estavam em classe funcional 111 e 7 pacientes em classe IV no pré… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In our initial experience, we observed two types of structural compromise of the skeletal muscle graft: significant atrophy and fibrosis and a significant reduction in the thickness of the skeletal muscle graft associated or not with lipid infiltration [25].…”
Section: Commentsmentioning
confidence: 95%
See 2 more Smart Citations
“…In our initial experience, we observed two types of structural compromise of the skeletal muscle graft: significant atrophy and fibrosis and a significant reduction in the thickness of the skeletal muscle graft associated or not with lipid infiltration [25].…”
Section: Commentsmentioning
confidence: 95%
“…CHACHQUES et al [24] reported the probability of surviving for seven years of follow up of 54%, whilst MOREIRA et al [25] reported a rate of 23% in the same period. The main causes of death during the late follow up period after dynamic cardiomyoplasty are heart failure, and sudden death, although arrhythmia was not correlated to the severity of ventricular dysfunction [4].…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation